If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = -7v Solving 56 = -7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7v' to each side of the equation. 56 + 7v = -7v + 7v Combine like terms: -7v + 7v = 0 56 + 7v = 0 Add '-56' to each side of the equation. 56 + -56 + 7v = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 7v = 0 + -56 7v = 0 + -56 Combine like terms: 0 + -56 = -56 7v = -56 Divide each side by '7'. v = -8 Simplifying v = -8
| (9x+5)(x+5)=0 | | 5x+3.5=8+x | | 35=16m | | 10x-18=12x+28 | | -3+2y=-8 | | 6-m=-11 | | 3*x^2-85*x-79=0 | | 3*x^2-85*x-316=0 | | (2x+10)(3x-4)=0 | | 3*x^2-91*x-316=0 | | 5+3(x+4)+2x=6(x-3)+5 | | A=288pir^2(7) | | A=288pir^27 | | 10+3(4x-6)+7=35 | | 17+5x=6x-13 | | -30*a^14*b^8/10*a^17*b^-5= | | 3(3x-4)-5=2(2-x) | | 21x^2=-11x+40 | | 293=4(x)+3 | | 3/48=(1/2)n | | 7(x+2)-3x-1=6(x+4)-4x+3 | | 36x^2+x-117=0 | | 4(3.75)-5(2.5)=4 | | 4+5y=-2y+18 | | 2x-3-4x=5 | | x^2+x=x^2-2x+6 | | (4/6)x=(5/6)y | | (4/6)x(5/6)y | | (X-3)(2x+9)=9(3x+2) | | y-10=9y-6 | | ml=7.3l | | 9w=2*9w |